Study on synthesis of rare earth tungsten heteropoly acid glycine composite catalyst and degradation of dyes. Issue 15 (17th December 2021) - Wang, Hao; Yang, Wan-Li; Ma, Rong-Hua; Tang, Yi-Min; Zhang, Cheng-Li
Abstract: Using glycine molecules as the carrier, a 1:11 rare earth tungsten heteropoly acid glycine composite catalyst was prepared by hydrothermal synthesis and characterized by XRD, TG, TEM, XPS and other methods. The effects of catalyst dosage, initial dye concentration, initial pH and other factors on the decolorization rate of Congo red simulated dye wastewater were investigated. The experimental results show that when the initial pH is 4, the amount of catalyst is 10 mg, and the dye concentration is 10 mg/L, the catalyst has good degradation performance on Congo red simulated dye wastewater, and the degradation can reach 90.9%. Graphical Abstract: UF0001